Robert Wagner and the Rise of New York City’s Plebiscitary Mayoralty: The Tamer of the Tammany Tiger - Flanagan, Richard M. author. aut Link
VI, 135 p. 1 illus.
Keywords: Robert Wagner was New York City's true New Deal mayor, killed Tammany Hall. The world Wagner shaped delivers municipal services efficiently at the cost of local democracy. The story of Wagner's mayoralty will be of interest to anyone who cares about New York City, local democracy and the debate about the legacy of the City's important leaders.